GW27-e0808 The Investigation of the Precaution of Exercise Preconditioning to the Myocardial Injury of Military Training Personnel Due to the High Intensity Exercise - Wu, Xuening; Cao, Xuebin (Journal of the American College of Cardiology, 2016)
Results Armed 5 kilometers before training without preconditioning training group and armed 5 kilometers before training after training preconditioning group heart rate variability, symptoms score, the score of ECG had significant difference (P<0.05), total heart rate and average heart rate had no significant difference (P>0.05); Armed 5 kilometers before training after preconditioning the training group of sinus arrhythmia, ventricular premature beat, ST-T change rate was less than 5 kilometers armed before training without pre adaptation training group (P<0.05), armed 5 kilometers before training without preconditioning training group and armed 5 kilometers before training after the pre adaptation training group the incidence of atrial premature beat had no significant difference (P>0.05); Armed 5 kilometers before training without pre adaptation training group the correlation analysis of heart rate variability and cardiac total number, average heart rate, symptoms score and the score of ECG.